Attitude to tattooing in modern Russian society: Regional aspect - V. V. Levchenko (Вестник университета)
The article considers theoretical and applied basis for analyzing tattooing phenomenon as one of the most widespread bodily practices in modern society. The patterns of attitude to this phenomenon and characteristic of modern society have been highlighted. Certain limitations of these studies and their fragmentation have been noted. The integral variant of this phenomenon analysis, including four components of the attitude to tattoo (cognitive, emotional, behavioral, and motivational) and considering peculiarities of social attitudes of the three main subjects occupying different positions in relation to tattoo (tattoo masters, their clients and a control group without tattoos) has been offered. The empirical study results have been presented, which made it possible to reveal regional specificity of the structure of attitude to the phenomenon of Perm residents (according to such parameters as cognitive component of attitude to tattoo (awareness of tattooing), emotional (assessment of tattoo as a social phenomenon; emotional attitude of relatives, close environment, and respondent to tattoo), behavioral (presence of tattoos; tattooed body parts; desire to get/remove a tattoo in the future), motivational (reasons for getting a tattoo; motives for choosing tattoo design in the future), and motivational ones (reasons for getting a tattoo; motives for getting a tattoo in the future).